2005
DOI: 10.1073/pnas.0506078102
|View full text |Cite
|
Sign up to set email alerts
|

Statistical coil model of the unfolded state: Resolving the reconciliation problem

Abstract: An unfolded state ensemble is generated by using a self-avoiding statistical coil model that is based on backbone conformational frequencies in a coil library, a subset of the Protein Data Bank. The model reproduces two apparently contradicting behaviors observed in the chemically denatured state for a variety of proteins, random coil scaling of the radius of gyration and the presence of significant amounts of local backbone structure (NMR residual dipolar couplings). The most stretched members of our unfolded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
416
2
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(439 citation statements)
references
References 51 publications
20
416
2
1
Order By: Relevance
“…[11][12][13] solution, 23 and a constant value of (R G /N 1/2 ) RIS calculated for the rotational-isomeric-state model in the limit of large N. 24 It may be seen that the experimental values of R G /N 1/2 are about equal to H0.7(R G /N 1/2 ) STAT . Thus, if (R G /N 1/2 ) STAT is presumed to be an accurate measure of R G /N 1/2 for the chain without any intramolecular association producing ring structures, g ¼ R 2 G /(R 2 G ) LIN % 0.7, larger than the value g ¼ 1/2 expected for a pure ring-shaped polymer.…”
Section: The Effects Of Association Among Chain Residuesmentioning
confidence: 95%
“…[11][12][13] solution, 23 and a constant value of (R G /N 1/2 ) RIS calculated for the rotational-isomeric-state model in the limit of large N. 24 It may be seen that the experimental values of R G /N 1/2 are about equal to H0.7(R G /N 1/2 ) STAT . Thus, if (R G /N 1/2 ) STAT is presumed to be an accurate measure of R G /N 1/2 for the chain without any intramolecular association producing ring structures, g ¼ R 2 G /(R 2 G ) LIN % 0.7, larger than the value g ¼ 1/2 expected for a pure ring-shaped polymer.…”
Section: The Effects Of Association Among Chain Residuesmentioning
confidence: 95%
“…18,19 In conclusion, we suggest that increasingly accurate random coil chemical shift scales will be obtained through approaches of the type that we have presented here by exploiting the continuous growth of databases of protein structures and chemical shifts, which will enable progressively more sophisticated functions to be parametrized. …”
mentioning
confidence: 97%
“…To reconcile the seemingly controversial properties of denatured proteins -the random coil scaling of their sizes and the presence of residual native structures -several computational works have recently been reported [203][204][205][206][207]. Fitzkee and Rose [206] reproduced the random coil scaling exponent using a denatured protein model with fixed secondary structure elements for a set of proteins.…”
Section: Unfolded Protein Statesmentioning
confidence: 99%
“…Tran et al [204,207] constructed the protein denatured state ensemble at atomic resolution in the excluded volume limit. Jha et al [205] built the denatured state using a statistical coil library. Both the Pappu and Sosnick groups found that the putative denatured state ensemble features transient local structures such as turns, strand, and helices.…”
Section: Unfolded Protein Statesmentioning
confidence: 99%
See 1 more Smart Citation